Protein Predictive Modeling and Simulation of Mutations of Presenilin-1 Familial Alzheimer’s Disease on the Orthosteric Site - Soto-Ospina, Alejandro; Araque Marín, Pedronel; Bedoya, Gabriel; Sepulveda-Falla, Diego; Villegas Lanau, Andrés (Frontiers in Molecular Biosciences, 2021)
Alzheimer’s disease pathology is characterized by -amyloid plaques and neurofibrillary tangles. Abnormal processing of the Amyloid Precursor Protein by the enzymes β and γ secretases, result in the production of β-amyloid peptides of length of 38-43 amino acids. Presenilin 1 (PS1) is the catalytic unit of γ-secretase and more than 200 PS1 pathogenic mutations have been identified as causative for Alzheimer’s disease. A complete monocrystal structure of PS1 has not been determined so far due to the presence of two flexible domains. We have developed a complete structural model of PS1 using a computational approach with structure prediction software. Missing fragments Met1-Glut72 and Ser290-Glu375 were modeled and validated by their energetic and stereochemical characteristics. Then, with the complete structure of PS1, we defined that these fragments do not have a direct effect in the structure of the pore. Next, we used our hypothetical model for the analysis of the functional effects of PS1 mutations Ala246Glu, Leu248Pro, Leu248Arg, Leu250Val, Tyr256Ser, Ala260Val and Val261Phe, localized in the catalytic pore. For this we used a Quantum Mechanics-Molecular Mechanics (QM/MM) hybrid method, evaluating modifications in the topology, potential surface density and electrostatic potential map of mutated PS1 proteins. We found that each mutation exerts changes resulting in structural modifications of the active site and in the shape of the pore. We suggest this as a valid approach for functional studies of PS1 in view of the possible impact in substrate processing and for the design of targeted therapeutic strategies.